VD_FINDINFO Ord / 2013 / 18 vom 25. Oktober 2013 - VD Tribunal cantonal (2013)
PRÉFET, DÉFAUTCONTUMACE, ORDONNANCE DE CONDAMNATION, OPPOSITIONPROCÉDURE | 355 al. 2 CPP (CH), 393 al. 1 let. a CPP (CH), 395 let. a CPP (CH)